MODEL MANAJEMEN PEMBINAAN PRAMUKA BERDIFERENSIASI UNTUK PESERTA DIDIK DENGAN HAMBATAN BERAGAM: STUDI MULTI-KASUS DI SLBN BAG B GARUT DAN SLB C YKB GARUT - Iman Gunawan; Risca Rosinta Agustin; Okke Rosmaladewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of differentiated-based Scouting coaching for students with diverse disabilities through a multi-case study at SLBN BAG B Garut and SLB C YKB Garut. Employing a qualitative approach with a case study design, data were collected through semi-structured interviews, participatory observation, and document analysis. The findings reveal that: (1) planning begins with needs assessment tailored to the type of disability; (2) organizing adopts different structures formal structure at the hearing impairment school versus small-group structure at the intellectual disability school; (3) implementation applies differentiation of content, process, and product, with communication strategies as the main differentiator; (4) evaluation is conducted continuously, both formally and informally. Supporting factors include the commitment of school principals/foundations and the enthusiasm of coaches, while inhibiting factors include limited human resources and the unavailability of special modules. This study contributes to the development of a contextual differentiated management model for Scouting coaching in special needs schools.